Innate immunity to Candida albicans - Yusuke Kiyoura; Riyoko Tamai (Elsevier, 2015)
Candida albicans is not a pathogen in healthy individuals, but can cause severe systemic candidiasis in immunocompromised patients. C. albicans has various virulence factors and activates the innate immune system. Specifically, C. albicans induces proinflammatory cytokine production in various cell types via many receptors, such as Toll-like receptors (TLRs) and C-type lectin receptors (CLRs). This microorganism also promotes phagocytosis via CLRs on macrophages. In a previous study, we found that C. albicans induces the production of galectin-3, which is a known CLR that kills C. albicans. This review indicates that the use of mouthwash containing an antimicrobial peptide or protein might be a useful new oral care method for the prevention of oral candidiasis.